2014
DOI: 10.3892/etm.2014.2013
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent low-dose digoxin may be effective and safe in patients with chronic heart failure undergoing maintenance hemodialysis

Abstract: A low dose of digoxin is known to reduce mortality and hospitalization in patients with heart failure; however, the safety of digoxin in treating patients with heart failure on maintenance hemodialysis remains controversial. The objective of this study was to determine the effectiveness and safety of digoxin at lower doses in patients with heart failure on maintenance hemodialysis using a retrospective cohort study. This study included 67 heart-failure patients on maintenance hemodialysis: Twenty-four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…According to the curvilinearity of the Frank–Starling relationship, if the heart is operating on the initial and steep part of the curve, it should have some preload reserve, and an increase in cardiac preload results in an increase in SV. [ 18 , 37 ] Previous studies of hemodynamic effects of PLR indicated that hemodynamic changes related to PLR were only induced by increased cardiac preload. [ 38 ] CO in response to PLR was according to the central volume status and the degree of cardiac preload reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the curvilinearity of the Frank–Starling relationship, if the heart is operating on the initial and steep part of the curve, it should have some preload reserve, and an increase in cardiac preload results in an increase in SV. [ 18 , 37 ] Previous studies of hemodynamic effects of PLR indicated that hemodynamic changes related to PLR were only induced by increased cardiac preload. [ 38 ] CO in response to PLR was according to the central volume status and the degree of cardiac preload reserve.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 17 ] The hemodynamic parameters CO, cardiac index (CI), stroke volume (SV), stroke volume index (SVI), left stroke work (LSW), and left stroke work index (LSWI) correlated positively with cardiac function. [ 18 ] Stroke systemic vascular resistance (SSVR) represents the resistance of blood flow in the vascular system. Stroke systemic vascular resistance index (SSVRI) is the systemic vascular resistance normalized for body surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al ( 12 ) reported that a low dose (125 μg po qod) of DGX was related to lower risk of mortality and hospitalization under condition of lower serum DGX concentration (SDC). In dialysis patients with HF receiving lower-dose DGX treatment (62.5 μg po qod), patients with iDGX had fewer DGX-related poisoning symptoms and were safer compared to those with cDGX ( 13 ). These findings suggested that the DGX use in HF management may be dynamic and change with congestion status.…”
Section: Introductionmentioning
confidence: 99%
“…As digoxin is primarily renally excreted, recommendations regarding dosage adjustment exists for varying degrees of renal function with limited guidance for dosage adjustments in intermittent hemodialysis (iHD) [7]. However, there is scarce published data regarding digoxin dosage adjustment and monitoring for the in CRRT, mostly in the form of case reports and series [7][8][9]. The purpose of this study is to evaluate the safety of administering digoxin in patients with A b-RVR undergoing CRRT therapy and e cacy in attaining rate control.…”
Section: Introductionmentioning
confidence: 99%